2009
DOI: 10.1111/j.1460-9568.2009.06836.x
|View full text |Cite
|
Sign up to set email alerts
|

Bar pressing for food: differential consequences of lesions to the anterior versus posterior pedunculopontine

Abstract: The pedunculopontine tegmental nucleus (PPTg) is in a key position to participate in operant reinforcement via its connections with the corticostriatal architecture and the medial reticular formation. Indeed, previous work has demonstrated that rats bearing lesions of the whole PPTg are impaired when learning to make two bar presses for amphetamine reinforcement. Anterior and posterior portions of the PPTg make different anatomical connections, including preferential projections by the anterior PPTg to substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 22 publications
(38 reference statements)
5
56
0
Order By: Relevance
“…It is likely that a different process is mediated by VTA mAChRs-possibly one that is more generally activating, given the large and prolonged elevation of DA release. (2) It is also consistent with experiments showing that excitotoxic lesions of posterior PPTg (a source of cholinergic input to VTA) but not anterior PPTg impair learning reinforced by natural rewards or drugs (Alderson et al 2008;Wilson et al 2009;Winn et al 2009). (3) Electrophysiological data in primates show that PPTg neurons respond in a proportionally graded manner either to signals predicting reward or to reward delivery (Okada et al 2009)-two pieces of information critical to forming predictive associations.…”
Section: Discussionsupporting
confidence: 84%
“…It is likely that a different process is mediated by VTA mAChRs-possibly one that is more generally activating, given the large and prolonged elevation of DA release. (2) It is also consistent with experiments showing that excitotoxic lesions of posterior PPTg (a source of cholinergic input to VTA) but not anterior PPTg impair learning reinforced by natural rewards or drugs (Alderson et al 2008;Wilson et al 2009;Winn et al 2009). (3) Electrophysiological data in primates show that PPTg neurons respond in a proportionally graded manner either to signals predicting reward or to reward delivery (Okada et al 2009)-two pieces of information critical to forming predictive associations.…”
Section: Discussionsupporting
confidence: 84%
“…Animal studies have provided an increasingly sophisticated understanding of the processes underlying normal human motivation and its disruption or dysregulation in apathy. PPN lesions block the motivational effects of ethanol [28,29], morphine, amphetamine [30] and reward learning [31] and cause motivational dysfunction [32] in rats. Other pontine regions involved in motivation and reward are the dorsal raphe nuclei [33].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used this toxin to assess specifically the contributions of cholinergic neurons within pPPTg to instrumental learning and the locomotor response to systemic nicotine. In experiment 1, rats were tested in an exact replication of the instrumental learning protocol in which we demonstrated a persistent learning impairment after excitotoxic lesion of pPPTg (Wilson et al 2009). In experiment 2, the rate and extent of locomotor sensitization to repeated systemic nicotine were assessed in a replication of the protocol used by Alderson et al (2008), which found altered sensitization in excitotoxic pPPTg-lesioned rats.…”
Section: Introductionmentioning
confidence: 99%
“…Excitotoxic lesions restricted to the posterior PPTg (pPPTg) impair the ability to learn foodrewarded instrumental tasks (Wilson et al 2009). Such lesions also alter the locomotor response to repeated systemic nicotine-reducing the initial hypolocomotion and increasing subsequent hyperlocomotion (Alderson et al 2008).…”
Section: Introductionmentioning
confidence: 99%